2014
DOI: 10.1017/jfm.2014.194
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of collisional particle dynamics in cluster-induced turbulence

Abstract: We present a computational study of cluster-induced turbulence (CIT), where the production of fluid-phase kinetic energy results entirely from momentum coupling with finite-size inertial particles. A separation of length scales must be established when evaluating the particle dynamics in order to distinguish between the continuous mesoscopic velocity field and the uncorrelated particle motion. To accomplish this, an adaptive spatial filter is employed on the Lagrangian data with an averaging volume that varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
100
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 31 publications
2
100
0
Order By: Relevance
“…In particular, it was shown in our previous work that three-dimensional EL simulations are capable of accurately reproducing key cluster characteristics, including fall velocity, mean cluster concentration and concentration fluctuations in wall-bounded gravity-driven flows (Capecelatro et al 2014b). The present paper is an extension of our previous work (Capecelatro et al 2014a), in which EL simulations of fully developed gravity-driven CIT were performed. Starting from a random distribution of particles subject to gravity, after an initial transient, the flow becomes statistically stationary with a probability density function (p.d.f.)…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…In particular, it was shown in our previous work that three-dimensional EL simulations are capable of accurately reproducing key cluster characteristics, including fall velocity, mean cluster concentration and concentration fluctuations in wall-bounded gravity-driven flows (Capecelatro et al 2014b). The present paper is an extension of our previous work (Capecelatro et al 2014a), in which EL simulations of fully developed gravity-driven CIT were performed. Starting from a random distribution of particles subject to gravity, after an initial transient, the flow becomes statistically stationary with a probability density function (p.d.f.)…”
mentioning
confidence: 83%
“…At higher values of mass loading, the relative motion between the phases leads to additional sources On fluid-particle dynamics in cluster-induced turbulence 581 4 7 10 14 0 FIGURE 1. (Colour online) Instantaneous field of fluid vorticity magnitude in gravity-driven CIT generated using data from Capecelatro, Desjardins & Fox (2014a) corresponding to Re p = 1 in this work (refer to table 1). Vorticity is generated by the shear layers at the edge of clusters, denoted by the blue lines showing iso-contours of α p = 3 α p .…”
mentioning
confidence: 99%
“…We have observed in previous studies that both the effective viscosity and turbulent viscosity contribute very little to the total viscosity in moderately dilute gas-solid flows, and the majority of fluid-phase turbulent kinetic energy is produced by resolved wakes past clusters (Capecelatro et al, 2014a). A detailed study on cluster-induced turbulence in a nonreactive homogeneous riser can be found in our previous work (Capecelatro et al, 2014b).…”
Section: Gas Phase Descriptionmentioning
confidence: 86%
“…Also in the absence of adequate knowledge about the mechanism of hydrodynamic interactions that lead to formation of particle clusters as of those observed by Capecelatro et al (2014), we assume that for Geldart A particle the major driving mechanism for formation of clusters is particle cohesion.…”
Section: Drag Model: Transition Between Uniform and Clustered Drag Lawsmentioning
confidence: 99%